(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
This paper investigates the postnational model of citizenship and contemporary challenges to postnational citizenship in the era of globalization whose nature is ambivalent and also includes fragmentation. Although the postnational concept of citizenship is based on the recognition of multiple identities, it does not necessarily represent the postmodern definition of citizenship, because, if this were the case, it would have to be based on the postmodern idea of decentred subjects, or fluid self. Unlike the postmodern citizenship, it is possible to imagine postnational citizenship that includes different identities, but perceives each of them as homogeneous. Economic and political dimensions of globalization and Europeanization coexist with resurgence of nationalism. The perception of paradox of nationalism in global era is further intensified by its European context as it was expected that the European Union overcomes nationalist discourses.